HUBUNGAN PAPARAN DEBU KAYU TERHIRUP DENGAN GANGGUAN FUNGSI PARU PADA PEKERJA DI INDUSTRI MEBEL CV. CITRA JEPARA FURNITURE KABUPATEN SEMARANG - Risa Kartika Putri; Yusniar Hanani Darundiati; Nikie Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Furniture industry workers have risk accumulation of dust in respiratory system which could cause impaired lung function. The purpose of this research was to analyze the correlation of respirable dust exposure with impaired lung function in furniture industry workers of CV. Citra Jepara Furniture Semarang Regency. This was an observational research with cross sectional design. Population of this research were 30 workers in sanding section and were taken as the research samples because it met the inclusion criteria. Data was analyzed using Chi Square test with α=0,05 to find out the correlation of independent variable and dependent variable. The results showed that there were 19 respondents (63,3%) who had respirable dust exposure above the NAB with average of respirable dust exposure was 2,506 mg/m3 and total of the lowest and highest dust exposure, respectively 0,775 and 5,426 mg/m3 . Result of lung function examination, 17 respondents (56,7%) had impaired lung function, with 10 people had obstruction, 4 people had restriction and 3 people had obstruction-restriction. Chi square test result showed a correlation of respirable dust exposure (p=0,023) with impaired lung function in furniture industry workers. It can be concluded the higher the exposure to respirable dust the greater the risk of impaired lung function.